Using an iPhone or iPad for Tonal Activities in Teaching Mandarin Chinese - William Beasley; Lih-Ching Chen Wang (International Journal of Education, 2024)
Tonal variation is a critical component of spoken Mandarin Chinese, but is relatively rare in Western languages such as English. Native speakers of Western languages who seek to learn Mandarin Chinese often find it particularly difficult to hear and reproduce the tonal variations that are required for fluency in the language. Auditory exercises focusing on detecting tonal variation in sound files can help such learners improve their ability to accurately perceive these variations over time. Recent developments in consumer technology, such as inexpensive smartphones and tablets, have provided tools that ease the process of creating and distributing such exercises. This article will describe the essence of the content to be employed in such learning activities and provide details of the process used to record and distribute them via smartphone.